MOVING STATUS OF CITIZENSHIP AS A FORM OF CRISIS OF INDONESIAN MUSLIM EMPLOYMENT IN MALAYSIA - Alfitra Alfitra (istinbath, 2022)
As citizens and society, every Indonesian citizen has the same position, rights, and obligations, that everyone is guaranteed the right to obtain citizenship status, to avoid the possibility of statelessness. While at the same time, every country must not allow its citizens have two citizenship status at once. Many Indonesian Muslim workers have moved their citizenship status to become Malaysian citizens. From this background, this study aims to identify and understand the policies that can be implemented by the two countries. This research is normative legal research using secondary data sources in the form of primary, secondary, and tertiary legal materials. Legal materials are obtained through documents or literature studies. While the approach used is the approach of legislation, history, and. The legal materials that have been collected are analyzed qualitatively, comprehensively, and completely. From the analysis conducted, three conclusions were obtained. The First, the factors that cause displacement, the citizenship status experienced by Indonesian citizens who have lived, and lived for decades in Malaysia is a form of a national identity crisis. The Second, laws and regulations that apply in Indonesia and Malaysia can also trigger the acceleration of becoming Malaysian citizens, so it can be concluded that the regulations made by the two countries also have a role in the transfer of Indonesian citizens to become Malaysian citizens. Third Impact for the two countries on the prevalence of the phenomenon of changing the status of citizens of Muslim Workers in Malaysia. Both Indonesia and Malaysia experience either negative or positive impacts on the migration of Indonesian citizens to Malaysia as follows: there are several positive and negative impacts caused by the transfer of citizenship.